Chinese Buddhist texts an introductory reader - Lock, Graham; Linebarger, Gary S. (Routledge, 2018)
The influence of Buddhism on the Chinese language, on Chinese literature and on Chinese culture in general cannot be overstated, and the language of most Chinese Buddhist texts differs considerably from both Classical and Modern Chinese. This reader aims to help students develop familiarity with features of Buddhist texts in Chinese, including patterns of organization, grammatical features and specialized vocabulary. It also aims to familiarize students with the use of a range of resources necessary for becoming independent readers of such texts. Chinese Buddhist Texts is suitable for students who have completed the equivalent of at least one year's college level study of Modern Chinese and are familiar with roughly one thousand of the commonest Chinese characters. Previous study of Classical Chinese would be an advantage, but is not assumed. It is an ideal textbook for students taking relevant courses in Chinese studies programs and in Buddhist studies programs. However, it is also possible for a student to work through the reader on his or her own. Further online resources are available at: lockgraham.com